Diagnostic Performance of Seven Commercial COVID-19 Serology Tests Available in South America - Rivera-Olivero, Ismar A.; Henríquez-Trujillo, Aquiles R.; Kyriakidis, Nikolaos C.; Ortiz-Prado, Esteban; Laglaguano, Juan Carlos; Vallejo-Janeta, Alexander Paolo; Lozada, Tannya; Garcia-Bereguiain, Miguel Angel, UDLA COVID-19 team (Frontiers in Cellular and Infection Microbiology, 2022)
Background. Although RT-qPCR remains the gold-standard for COVID-19 diagnosis, anti-SARS-CoV-2 serology-based assays have been massively used during 2020 as an alternative for individual and mass testing, and its currently used for seroprevalence population studies. Objective. To study the clinical performance of seven commercially available serological tests for COVID-19 diagnosis in South America. Methods. We conducted a blind evaluation of five rapid diagnostic tests (RDTs) and two enzyme-linked immunosorbent assays (ELISAs) commercially available in Ecuador and neighboring countries for detecting anti-SARS-CoV-2 antibodies. Results. We found no statistically significant differences among ELISA kits and RDTs kits for anti-SARS-CoV-2 IgG sensitivity (values ranging from 76.4% to 83.5%) and specificity (100% for the seven serological assays). For anti-SARS-CoV-2 IgM, the five RDTs have a significantly higher sensitivity for samples collected 15 days after the RT-qPCR test, with values ranging from 47.1% to 88.2%; moreover, the specificity varied from 85% to 100%, but the only brand with 100% specificity had the lowest sensitivity. Conclusion. The diagnostic performance of the seven serological tests was acceptable for the seven brands tested for anti-SARS-CoV-2 IgG detection for seroprevalence screening purposes. On the other hands, our results endorse the lack of accuracy of anti-SARS-CoV-2 IgM detection in RDTs as a tool for SARS-CoV-2 acute-phase infection diagnosis.